Crystal Structure of 5-Nitro-4-(4-methoxyphenoxy)phthalonitrile - Dmitry Erzunov; Anastasia Rassolova; Igor Abramov; Vladimir Maizlish; Roman Rumyantsev; Arthur Vashurin (Molbank)
This article presents findings on the synthesis and crystal structure analysis of 5-nitro-4-(4-methoxyphenoxy)phthalonitrile. The crystal structure was meticulously refined using X-ray diffraction techniques, which allowed for a detailed examination of the molecular arrangement within the crystal. The manuscript elaborates on the significant intermolecular and intramolecular interactions that contribute to the overall crystal packing, highlighting how these interactions influence the stability and properties of the material.